1998
DOI: 10.12693/aphyspola.94.749
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Acridine and its Aggregates Isolated in the Neon Matrix

Abstract: The results of experimental studies of fluorescence and phosphorescence of acridine in the low-temperature inert neon matrix, at 7 K, are reported. It is found that the low-temperature inert matrix of neon affects the energy levels of acridine molecules very weakly even as compared. with nonpolar (aprotic) and non-reactive solvent (e.g. hexane) and that there are different sites for acridine molecules in the neon matrix. However, the observed fluorescence spectra are strongly dependent on the excitation wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 27 publications
6
18
0
Order By: Relevance
“…A pronounced interchange in the bond alternation of the benzenic rings is expected to have a significant influence in the energy of the state and large vibrational progressions along the C−C stretching modes can be predicted. Finally, the geometrical changes in the B 2 π → π*(L b ) states are small, although a slight expansion of the molecule takes place, consistent with the results of vibrational spectroscopy, showing intense transitions and short Franck−Condon progressions. , The behavior of the L a and L b states is similar to that found in the equivalent states of analogous compounds. ,, …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…A pronounced interchange in the bond alternation of the benzenic rings is expected to have a significant influence in the energy of the state and large vibrational progressions along the C−C stretching modes can be predicted. Finally, the geometrical changes in the B 2 π → π*(L b ) states are small, although a slight expansion of the molecule takes place, consistent with the results of vibrational spectroscopy, showing intense transitions and short Franck−Condon progressions. , The behavior of the L a and L b states is similar to that found in the equivalent states of analogous compounds. ,, …”
Section: Resultssupporting
confidence: 78%
“…As regards the emission spectroscopy of acridine, most of the studies have been devoted to the description of the relative position of the low-lying singlet and triplet states and the definition of the photophysical paths and their dependence on the environmental conditions. ,, The intense fluorescence reported in protic solvents with large lifetimes has been attributed to the presence of a π → π* state as the lowest singlet state in polar environments. On the other hand, the low fluorescence quantum yield in the vapor and nonpolar solvents, ,, has been explained by a more stable n → π* state and the predominance of nonradiative processes such as intersystem crossings and internal conversions in these media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal modes analysis of the vibrations of ACD molecule and of its direr was performed utilizing a semiempirical ΡΜ3 method [9] which, despite some obvious deficiencies, is generally considered as suitable for handling the vibrational problems in weakly bound molecular and hydrogen-bound complexes and which we have utilized earlier for optimization of the ground-state geometry of acridine direr and calculations of its molecular orbitals, electronic states, and relevant transition dipole moments [4].…”
Section: Vibrational Analysis Of Acridine Molecule and Acridine Dirermentioning
confidence: 99%
“…Α preliminary analysis of the observed vibronic structure of LIF excitation spectra of (ΑCD)2 [2] was based on a comparison with the data available from the observations of the ground-state IR and Raman spectra in liquid and in 8olid phase [6,7] and from the analysis of the vibronic structure of electronic absorption and phosphorescence spectra in low-temperature crystalline and amorphous matrices [8,9]. This comparative analysis has shown that the observed structure of LIF excitation spectrum can be separated into two sets of vibrational modes -the low-frequency vibrational modes of clear intermolecular origin inherent to (ΑCD)2 and the vibrational modes which presumably are of intramolecular origin.…”
Section: Introductionmentioning
confidence: 99%